No missed opportunity: expanding sexual healthcare provision beyond current service delivery models - Heller, Rebecca Lily (The University of Edinburgh, 2018)
BACKGROUND: Despite a wide range of contraceptive options available in the United Kingdom, the unplanned pregnancy rate remains high. Contraceptive services are currently delivered by general practitioners, sexual health clinics and pharmacies, but there may be scope to expand the places that these are offered, and increase the options available within each service. Doing so could increase the uptake of contraceptive methods, particularly the most effective methods, and therefore reduce the unplanned pregnancy rate. AIM AND OBJECTIVES: Research in this thesis aimed to investigate novel delivery models of contraception. The research had two main areas of focus. Firstly the capacity of the pharmacy to deliver regular contraception was examined, in the context of existing literature, and then through a pilot study. After that the expansion of contraception care to maternity services was investigated, first in the literature and then using an observational study. METHODS: In undertaking this thesis I used a variety of methods. Two patient surveys were employed to investigate patients’ perspectives on proposed novel methods of contraceptive delivery. A pilot study investigated the feasibility and acceptability of delivery of the contraceptive injection at the pharmacy. Quantitative results about the numbers of injections given were collected, as were patient questionnaires. Qualitative one-to-one interviews were conducted with participating pharmacists, these were recorded, transcribed and analysed. An observational study was also undertaken to assess routine delivery of insertion of intra-uterine contraception at the time of caesarean section. Patients were seen at six weeks following insertion, and contacted by telephone at three, six and 12 months about satisfaction and continuation of the method. RESULTS: 220 women completed a questionnaire about attending the community pharmacy to receive a contraception injection. 33% of current non-users indicated that they would consider using this method if it was available at the pharmacy. 50 established users of the contraceptive injection participated in a pilot project receiving up to three injections from the community pharmacy. Only 48 injections of a possible 150 were delivered at the community pharmacy. Only 7 participants received all three injections at the pharmacy, and participants reported mixed experiences accessing the pharmacy. The practical obstacles around pharmacy engagement and the challenges of retaining participants were significant, and more research is necessary before proceeding with a randomised controlled trial. 250 women on a postnatal ward completed questionnaires about their pregnancy intentions. 96.7% were not planning a baby in the next year, but only 23.6% were planning on using the most effective methods of contraception. One in three respondents described themselves as likely to use either an implant or intra-uterine contraception if it could be inserted before they left the hospital. In an observational study, 120/877 women opted to have intra-uterine contraception inserted at the time of caesarean section. Continuation rates at 12 months were 84.8% of those contacted, and 92.6% were either ‘very’ or ‘fairly’ happy with their contraception. CONCLUSION: Although patients are receptive to contraception being delivered using novel service models, alternatives to current practice need careful investigation. Contraceptive injections at the community pharmacy are not necessarily more convenient for patients, and therefore may not increase uptake of this method. However, offering intrauterine contraception to patients at the time of caesarean section is highly acceptable to patients, and results in a substantial majority continuing this highly effective method. Robust and careful research using a range of methods can help to identify which innovative approaches to contraceptive delivery offer the most promise.
Keywords: unplanned pregnancy; contraception; pharmacy; intrauterine contraception; contraceptive services